Foamable polylactic acid bead material, foamed polylactic acid bead material and preparation methods of foamable polylactic acid bead material and foamed polylactic acid bead material
By filling the bonding layer of a specific structure between the polylactic acid particles, and using polymer A and carbon nanotube-coated polymer B to form a multiphase structure, the problem of difficulty in improving the conductivity and foaming properties in the prior art is solved, and the effect of efficient conductivity and foaming at extremely low conductive doses is achieved.
Patent Information
- Application Number
- CN202411851380.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-11
AI Technical Summary
The conductive and foaming properties of existing polylactic acid foamed bead materials are difficult to improve simultaneously, especially at extremely low conductive filler volume, the conductive and foaming properties of the materials are not ideal.
By filling the polylactic acid particles with a specific structure, the bonding layer consists of polymer B covered with polymer A as a continuous phase and functional group modified with carbon nanotubes as a dispersed phase, forming a multiphase structure to improve conductivity while maintaining high foaming properties.
It is achieved that the polylactic acid bead material has good conductivity under extremely low conductive agent filling amount, and the material obtained after foaming has high foaming performance and excellent conductivity.
Smart Images

Figure CN119798764A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive polylactic acid foaming materials, and in particular to a foamable polylactic acid bead material and a foamed polylactic acid bead material and respective preparation methods. Background Art
[0002] PLA is a bio-derived, biodegradable thermoplastic with mechanical properties similar to petroleum-based plastic polystyrene. The improvement of PLA's molding performance and high performance are conducive to solving plastic white pollution and getting rid of oil dependence. Among the various PLA products, expandable PLA beads (EPLA) have the advantages of ultra-high foaming ratio (30-60 times), complex molding structure, fine surface pattern products, etc., which can meet a variety of application scenarios. In particular, EPLA products with conductive properties can be used in the core components of human-machine interfaces, soft robots, electronic skins and real-time health monitoring equipment under the rapid development of advanced electronic devices: flexible piezoresistive sensors have great potential in manufacturing. Nevertheless, molded conductive EPLA products are limited by the performance trade-off between filler content and foam molding ability. In order to obtain better electrical signal sensitivity, the material needs to have a lower resistivity, so a large amount of conductive filler particles must be added. In this case, the rigidity of the material continues to increase, the expandability decreases, it is difficult to produce large-scale deformation in response to external pressure, and the sensitivity of the sensor decreases. At the same time, conductive filler particles, such as carbon black, carbon nanotubes (CNT), and graphene are easy to agglomerate, and excessive addition is also difficult to effectively improve the conductivity. Therefore, under traditional molding methods, it is difficult to improve both the conductive properties and the foaming properties at the same time.
[0003] At present, a certain degree of research has been carried out on improving the conductivity of foamed materials, but these methods are almost all about introducing a large amount of conductive fillers into the polymer. Different from the traditional method, some studies have proposed a new conductive filler addition strategy. CN114334226A discloses a method for preparing a flexible PLA transparent conductive film. In order to obtain better conductive properties, this technical method mainly uses a solvent method to mix PLA and graphene, and then evaporates the solvent to form a conductive film. This method adds 3.5wt% of graphene, and the conductivity of the PLA composite material only reaches 10 -5S / cm, and the film is difficult to foam into a piezoresistive sensor. CN115960435A discloses a method for improving the conductive efficiency of fillers. This technical method mainly utilizes electrochemical deposition to deposit a large amount of CNT and graphene on carbon fiber, uses carbon fiber as a conductive path template, and uses CNT and graphene to improve conductivity, thereby improving the conductive properties of polymer composite materials. However, the conductive path formed by this method is only carbon fiber. The carbon fiber is large in size and the conductive network efficiency is low. Therefore, at a filler addition of 0.5wt%, the resistivity of the system is still as high as 0.16Ω·cm. CN118027628A discloses a high-performance conductive PLA composite material with an oriented structure and a preparation method thereof. This technical method utilizes the stretching field of an extruder to form oriented fibers rich in CNTs in a PLA matrix, thereby improving the conductive path efficiency. However, under this method, the CNT content is as high as 4wt%, and PLA reaches the conductive percolation threshold of 2.1×10 -2 S / cm. To achieve the conductive properties of polymers, the key is not to fill a large amount of conductive fillers, but to form an efficient conductive network structure. Therefore, developing a method that can still form an efficient conductive path structure under extremely low conductive fillers and does not have a significant negative impact on the foaming properties of the polymer is of great support for the manufacturing and performance optimization of high-performance flexible piezoresistive sensors. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem in the prior art that the conductive properties and foaming properties of polylactic acid foamed bead materials cannot be improved at the same time, and to provide a foamable polylactic acid bead material and a foamed polylactic acid bead material and their respective preparation methods. The foamable polylactic acid bead material includes polylactic acid particles and an adhesive layer filled between the polylactic acid particles, and the adhesive layer has a polymer A with a specific structure as a continuous phase and a polymer B with a specific structure coated with carbon nanotubes as a dispersed phase, so that the foamable polylactic acid bead material obtained thereby has high conductive properties under the condition of a lower conductive agent filling amount, and the foamed polylactic acid bead material obtained after foaming can have both high foaming properties and excellent conductive properties.
[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a foamable polylactic acid bead material, wherein the foamable polylactic acid bead material comprises polylactic acid particles and a bonding layer filled between the polylactic acid particles;
[0006] The bonding layer includes a continuous phase and a dispersed phase, wherein the polymer A constituting the continuous phase includes a structural unit shown in Formula 1 and a structural unit shown in Formula 2, and the dispersed phase is a polymer B coated with a conductive agent, and the polymer B includes a structural unit shown in Formula 1 and a structural unit shown in Formula 3;
[0007]
[0008] Wherein, R1 is a C3-C5 alkylene group, R2 is a C1-C3 alkyl group, R3 is a C2-C4 alkyl group, and R4 is a C1-C4 alkyl group; the conductive agent is a conductive agent modified with a functional group;
[0009] Based on the total weight of the expandable polylactic acid bead material, the content of the polylactic acid particles is 50-75wt%, and the content of the bonding layer is 25-50wt%.
[0010] The second aspect of the present invention provides a method for preparing the above-mentioned expandable polylactic acid bead material, wherein the preparation method comprises the following steps:
[0011] (1) in the presence of water, an emulsifier and a surfactant, a monomer I represented by formula I, a monomer II represented by formula II and an initiator are mixed to carry out a first emulsion polymerization reaction to obtain an emulsion A containing a polymer A;
[0012] (2) in the presence of water, an emulsifier and a surfactant, mixing a conductive agent, a monomer I represented by formula I, a monomer III represented by formula III and an initiator, and performing a second emulsion polymerization reaction to obtain an emulsion B containing a polymer B coated with carbon nanotubes; the conductive agent is a conductive agent modified with a functional group;
[0013] (3) In a mold, the polylactic acid particles, emulsion A and emulsion B are mixed and dried to obtain the foamable polylactic acid bead material;
[0014]
[0015] Wherein, R1 is a C3-C5 alkylene group, R2 is a C1-C3 alkyl group, R3 is a C2-C4 alkyl group, and R4-R7 are each independently a C1-C4 alkyl group;
[0016] The amount of polylactic acid particles used is 150-190 parts by mass, the amount of emulsion A used is 30-50 parts by mass, and the amount of emulsion B used is 30-50 parts by mass.
[0017] The third aspect of the present invention provides a foamed polylactic acid bead material, wherein the foamed polylactic acid bead material is obtained by foaming the foamable polylactic acid bead material described in the first aspect.
[0018] The fourth aspect of the present invention provides a method for preparing the above-mentioned foamed polylactic acid bead material, wherein the preparation method comprises: mixing a foaming agent with the foamable polylactic acid bead material described in the first aspect, and foaming to obtain the foamed polylactic acid bead material.
[0019] Through the above technical scheme, the foamable polylactic acid bead material and the foamed polylactic acid bead material provided by the present invention and their respective preparation methods obtain the following beneficial effects:
[0020] Compared with the conventional method of directly melt-blending a large amount of CNT into a PLA matrix and combining it with the induced multi-melting peak PLA preparation technology, the foamable polylactic acid bead material provided by the present invention comprises polylactic acid particles and a bonding layer filled between the polylactic acid particles, and the bonding layer has a polymer A with a specific structure as a continuous phase and a polymer B with a specific structure coated with a conductive agent as a dispersed phase, thereby effectively avoiding the complex process of inducing multi-melting peak PLA resin. Specifically, the polymer B in the dispersed phase as a carrier can improve the dispersibility of the conductive agent in the continuous phase, and the structural unit shown in Formula 3 contained in the polymer B contains multiple hydroxyl groups, which can further improve the load and dispersion of the conductive agent on the polymer B particles, and finally realize that the conductive agent is distributed only on the surface of the continuous polymer B particles in a limited and continuous bonding layer, so that the foamable polylactic acid bead material has good conductive properties at an extremely low content, and the conductive agent foamed polylactic acid bead material obtained after foaming can have both high foaming performance and excellent conductive properties.
[0021] Compared with most technical methods of directly dispersing CNTs into PLA matrix, the EPLA foaming material obtained by the present invention can obtain 2.5×10 -2 The conductivity is S / m. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the formation of continuous confined space CNT conductive pathways in the EPLA bead bonding layer.
[0023] Figure 2 Photos of (a) EPLA beads, (b) PMMA, PEA and CNT emulsion filled between beads, (c) EPLA material after sintering, and (d) EPLA material after supercritical CO2 foaming.
[0024] Figure 3 Optical microscope photographs of the sintered layer in EPLA in (a) Example 1, (b) Example 3, (c) Example 5 and (d) Comparative Example 2.
[0025] Figure 4 It is a scanning electron microscope photo of the bonding layer of different conductive polylactic acid foam bead materials.
[0026] Figure 5 This is a scanning electron microscope photograph of the bonding layer of the polylactic acid foamed beads material in Example 1 at a magnification of 12,000 times. DETAILED DESCRIPTION
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] The first aspect of the present invention provides a foamable polylactic acid bead material, wherein the foamable polylactic acid bead material comprises polylactic acid particles and a bonding layer filled between the polylactic acid particles;
[0029] The bonding layer includes a continuous phase and a dispersed phase, wherein the polymer A constituting the continuous phase includes a structural unit shown in Formula 1 and a structural unit shown in Formula 2, and the dispersed phase is a polymer B coated with a conductive agent, and the polymer B includes a structural unit shown in Formula 1 and a structural unit shown in Formula 3;
[0030]
[0031] Wherein, R1 is a C3-C5 alkylene group, R2 is a C1-C3 alkyl group, R3 is a C2-C4 alkyl group, and R4 is a C1-C4 alkyl group;
[0032] The conductive agent is a conductive agent modified with functional groups;
[0033] Based on the total weight of the expandable polylactic acid bead material, the content of the polylactic acid particles is 50-75wt%, and the content of the bonding layer is 25-50wt%.
[0034] In the present invention, the foamable polylactic acid bead material includes polylactic acid particles and a bonding layer filled between the polylactic acid particles, and the bonding layer has a polymer A with a specific structure as a continuous phase, and a polymer B with a specific structure coated with a conductive agent modified by a functional group as a dispersed phase, which effectively avoids the complex process of inducing multiple melting peaks of PLA resin. Specifically, the polymer B in the dispersed phase serves as a carrier to improve the dispersibility of the conductive agent (such as carboxylated carbon nanotubes CNT) in the continuous phase, and the structural unit shown in Formula 3 contained in the polymer B contains multiple hydroxyl groups, which can further improve the loading and dispersion of the carbon nanotubes on the polymer B particles, and finally realizes that the conductive agent is only distributed on the surface of the continuous polymer B particles in a limited and continuous bonding layer, so that the foamable polylactic acid bead material has good conductive properties at an extremely low conductive agent content, and the foamed polylactic acid bead material obtained after foaming can have both high foaming performance and excellent conductive properties.
[0035] In the present invention, when the contents of the polylactic acid particles and the adhesive layer in the expandable polylactic acid bead material are controlled to meet the above range, it can be ensured that the adhesive layer is fully filled in the gaps formed between the polylactic acid particles, so that the expandable polylactic acid beads have good adhesion.
[0036] Specifically, when the content of the polylactic acid particles and the bonding layer meets the above range, the multiphase structure in the bonding layer with polymer A as the continuous phase and polymer B coated with carbon nanotubes as the dispersed phase can be fully filled in the continuous space formed around the polylactic acid particles. Specifically, the volume of the multiphase structure accounts for about 30-40% of the volume of the continuous space formed around the polylactic acid particles.
[0037] Further, R1 is a C3-C4 alkylene group, R2 is a C1-C2 alkyl group, R3 is a C2-C3 alkyl group, and R4 is a C1-C3 alkyl group.
[0038] In a specific embodiment of the present invention, R1 is a C3 alkylene group, R2 is a methyl group, R3 is an ethyl group, and R4 is a methyl group.
[0039] Furthermore, based on the total weight of the expandable polylactic acid bead material, the content of the polylactic acid particles is 63-75wt%, and the content of the bonding layer is 25-37wt%.
[0040] According to the present invention, based on the total weight of polymer A, the content of the structural unit represented by formula 1 is 3-10 wt %, and the content of the structural unit represented by formula 2 is 90-97 wt %.
[0041] In the present invention, when the contents of the structural unit represented by Formula 1 and the structural unit represented by Formula 2 in polymer A meet the above range, polymer A contains a large number of active groups that can react with the carboxyl groups on the surface of the conductive agent, so that a strong bond is formed between polymer A and polymer B coated with the conductive agent, thereby forming a stable conductive path.
[0042] Furthermore, based on the total weight of polymer A, the content of the structural unit represented by formula 1 is 4-6 wt %, and the content of the structural unit represented by formula 2 is 94-96 wt %.
[0043] According to the present invention, based on the total weight of polymer B, the content of the structural unit represented by formula 1 is 3-10 wt %, and the content of the structural unit represented by formula 3 is 90-97 wt %.
[0044] In the present invention, when the contents of the structural unit represented by the formula in polymer B and the structural unit represented by formula 3 meet the above range, polymer B contains a large number of active sites that can react with the carboxyl groups on the surface of the conductive agent, thereby improving the coating effect of the conductive agent on the polymer, and forming a uniformly dispersed conductive agent coating layer on the surface of polymer B.
[0045] Furthermore, based on the total weight of polymer B, the content of the structural unit represented by formula 1 is 4-6 wt %, and the content of the structural unit represented by formula 3 is 94-96 wt %.
[0046] According to the present invention, the polymer B is in granular form with an average particle size of 5-200 μm.
[0047] In the present invention, when the particle size of polymer B particles meets the above range, the loading rate of the conductive agent on the surface of the polymer particles can be increased, thereby making it easier for the polymer B coated with the conductive agent in the foamable polylactic acid bead material to form a conductive path, thereby improving the conductive properties of the foamable polylactic acid bead material.
[0048] Furthermore, the average particle size of the polymer B is 30-80 μm.
[0049] According to the present invention, based on the total weight of polymer B, the content of the conductive agent is 0.5-15 wt%.
[0050] In the present invention, when the content of carbon nanotubes meets the above range, the conductive agent can have a high loading rate on the surface of polymer B, thereby improving the conductive properties of the expandable polylactic acid bead material.
[0051] Furthermore, based on the total weight of the polymer B, the content of the conductive agent is 1-1.8 wt %.
[0052] According to the present invention, the functional group is selected from an amine group and / or a carboxyl group.
[0053] According to the present invention, the conductive agent is selected from at least one of carbon nanotubes, carbon black and graphene.
[0054] In a preferred embodiment of the present invention, the conductive agent is carboxylated carbon nanotubes.
[0055] In the present invention, carboxylated carbon nanotubes are used, and the carboxyl groups in the carbon nanotubes can chemically react with the structural unit I in the polymer A and polymer B particles, further enhancing the interaction between the carbon nanotubes and the polymer B particles and the polymer A as the continuous phase, thereby improving the dispersibility of the carbon nanotubes in the adhesive layer.
[0056] According to the present invention, the mass ratio of the continuous phase to the dispersed phase is 0.5-1.5:1.
[0057] In the present invention, when the mass ratio of the continuous phase and the dispersed phase satisfies the above-mentioned range, it is possible to increase the content of the conductive agent particles in the foamable polylactic acid bead material while ensuring that the dispersed phase is evenly dispersed in the continuous phase, and to ensure good adhesion between the polylactic acid particles while ensuring the conductive properties of the foamable polylactic acid bead material.
[0058] Furthermore, the mass ratio of the continuous phase to the dispersed phase is 1-1.2:1.
[0059] According to the present invention, the average particle size of the polylactic acid particles is 0.1-5 mm.
[0060] In the present invention, when the particle size of the polylactic acid particles meets the above range, the bonding layer can be more easily filled in the gaps between the polylactic acid particles, thereby improving the particle bonding between the polylactic acid particles.
[0061] Furthermore, the average particle size of the polylactic acid particles is 1-4 mm.
[0062] In the present invention, based on the total weight of the expandable polylactic acid bead material, the content of the conductive agent is 0.04-1wt%, preferably 0.05-0.8wt%.
[0063] The second aspect of the present invention provides a method for preparing the above-mentioned expandable polylactic acid bead material, wherein the preparation method comprises the following steps:
[0064] (1) in the presence of water, an emulsifier and a surfactant, a monomer I represented by formula I, a monomer II represented by formula II and an initiator are mixed to carry out a first emulsion polymerization reaction to obtain an emulsion A containing a polymer A;
[0065] (2) in the presence of water, an emulsifier and a surfactant, mixing a conductive agent, a monomer I represented by formula I, a monomer III represented by formula III and an initiator, and performing a second emulsion polymerization reaction to obtain an emulsion B containing a polymer B coated with carbon nanotubes;
[0066] (3) In a mold, the polylactic acid particles, emulsion A and emulsion B are mixed and dried to obtain the foamable polylactic acid bead material;
[0067]
[0068] Among them, R1 is a C3-C5 alkylene group, R2 is a C1-C3 alkyl group, R3 is a C2-C4 alkyl group, and R4-R7 are each independently a C1-C4 alkyl group.
[0069] In the present invention, monomers I and II, as well as monomers I, III and carbon nanotubes are respectively polymerized by emulsion polymerization to obtain emulsions A and emulsions B, wherein conductive agent-coated polymer B particles are formed in emulsion B, emulsions A and emulsions B are injected into a mold containing polylactic acid particles, and emulsions A and emulsions B are filled into gaps formed between polylactic acid particles. During the drying process, as the solvent evaporates, polymer A in emulsion A and conductive agent-coated polymer B particles in emulsion B contact and fuse with each other, and structural unit I contained in polymer A reacts with the conductive agent coated on the surface of polymer B particles, and finally a multiphase structure with polymer A as a matrix and conductive agent-coated polymer B particles as a dispersed phase is formed in the gaps between polylactic acid particles. The existence of this structure can further improve the dispersion effect of the conductive agent by spherical arrangement in the continuous space outside the polylactic acid particles (the gaps between particles), so that a continuous conductive network structure is formed in a narrow space. The final effect is to form an efficient conductive network structure at a very low conductive agent filling amount, so that the conductivity of the foamed material obtained by foaming the expandable polylactic acid bead material is greatly improved. At the same time, because the conductive agent is not dispersed in the polylactic acid (PLA) matrix, it does not affect the foaming performance of the expandable polylactic acid bead material. This method can achieve good formability, mechanical properties and conductive properties of the polylactic acid bead foam material.
[0070] In the present invention, there is no particular limitation on the order of step (1) and step (2), and the order of step (1) and step (2) can be adjusted according to actual needs.
[0071] Further, R1 is a C3-C4 alkylene group, R2 is a C1-C2 alkyl group, R3 is a C2-C3 alkyl group, and R4-R7 are each independently a C1-C3 alkyl group.
[0072] In a specific embodiment of the present invention, the monomer I shown in formula I is 3-(trimethoxysilyl)propyl methacrylate, that is, R1 is propylene, and R2, R5-R7 are all methyl.
[0073] In a specific embodiment of the present invention, the monomer II shown in formula II is ethyl acrylate, that is, R3 is ethyl.
[0074] In a specific embodiment of the present invention, the monomer III shown in formula III is methyl methacrylate, that is, R4 is methyl.
[0075] According to the present invention, the emulsifiers in step (1) and step (2) are each independently selected from at least one of sodium dodecylbenzene sulfonate, alkylbenzene sulfonate and fatty acid salt.
[0076] In the present invention, the specific type of emulsifier used is easily soluble in water and can reduce interfacial tension, so that monomer I, monomer II and monomer III can form stable micelles during the polymerization process, improve the stability of the emulsion, and prevent the occurrence of droplet aggregation.
[0077] In a specific embodiment of the present invention, the emulsifier in step (1) and step (2) is sodium dodecylbenzene sulfonate.
[0078] According to the present invention, the surfactants in step (1) and step (2) are each independently selected from at least one of polyvinyl alcohol, methyl cellulose and gelatin.
[0079] In the present invention, the above-mentioned specific type of surfactant has both a hydrophilic group and a lipophilic group, and can be adsorbed on the surface of latex particles to form a protective film on the surface of latex particles, thereby further reducing interfacial tension and improving emulsion stability.
[0080] In a specific embodiment of the present invention, the surfactant in step (1) and step (2) is polyvinyl alcohol.
[0081] According to the present invention, the initiators in step (1) and step (2) are each independently selected from at least one of ammonium persulfate, potassium persulfate and azobisisobutyronitrile.
[0082] In a specific embodiment of the present invention, the initiator in step (1) and step (2) is ammonium persulfate.
[0083] According to the present invention, in step (2), the functional group is selected from carboxyl and / or amine.
[0084] According to the present invention, the conductive agent is selected from at least one of carbon nanotubes, carbon black and graphene.
[0085] In a preferred embodiment of the present invention, the conductive agent is a carboxyl-modified carbon nanotube. In the present invention, the carboxyl-modified carbon nanotube is used, and the carboxyl group in the carbon nanotube can chemically react with the structural unit I in the polymer A and polymer B particles, further improving the interaction between the carbon nanotube and the polymer B particles and the polymer A as a continuous phase, and improving the dispersibility of the carbon nanotube in the adhesive layer.
[0086] According to the present invention, the conditions of the first emulsion polymerization reaction and the second emulsion polymerization reaction independently include: reaction temperature of 60-85° C., reaction time of 2-4 h, and pH of 3-5.
[0087] In the present invention, when the conditions for controlling the first emulsion polymerization reaction and the second emulsion polymerization reaction independently satisfy the above ranges, the polymerization rate can be controlled, and the polymerization degree and conversion rate of the monomers can be increased without destroying the stability of the emulsion.
[0088] Furthermore, the conditions of the first emulsion polymerization reaction and the second emulsion polymerization reaction independently include: reaction temperature of 70-80° C., reaction time of 2.5-3.5 h, and pH of 3.5-4.5.
[0089] According to the present invention, the drying conditions include: a drying temperature of 50-70° C. and a drying time of 4-8 hours.
[0090] In the present invention, when the drying conditions are controlled to meet the above-mentioned range, it is possible to ensure that the polylactic acid does not undergo thermal deformation, and at the same time, the structural unit shown in Formula 1 in the polymer A can fully react with the conductive agent, while allowing the water to evaporate quickly, ultimately allowing the particles of the foamable polylactic acid beads to have excellent bonding strength, while the conductive agent forms a good conductive path between the polylactic acid beads.
[0091] Furthermore, the drying conditions include: a drying temperature of 55-65° C. and a drying time of 5-7 hours.
[0092] In the present invention, preferably, step (1) and step (2) are carried out under stirring conditions. There is no particular limitation on the stirring rate, as long as the raw materials can be fully dissolved or evenly dispersed. For example, the stirring rate is 500-1500 rpm.
[0093] According to the present invention, in step (1), based on the total amount of monomer I and monomer II, the amount of monomer I is 1-10 wt%.
[0094] According to the present invention, based on the total amount of monomer I and monomer II, the amount of emulsifier is 0.01-0.1wt%, the amount of initiator is 0.01-0.1wt%, and the amount of surfactant is 0.01-1wt%.
[0095] In the present invention, when the amount of each substance is controlled to meet the above-mentioned range, the content of the structural unit from monomer I (the structural unit shown in Formula 1) in the prepared foamable polylactic acid bead material can be moderate, sufficient to react with the structural unit from monomer I in polymer B, and the colloidal particles in the emulsion and the polymer A emulsion have excellent stability, ensuring that polymer A can form a stable adhesive layer and improving the dispersibility of the conductive agent in the bead material.
[0096] Furthermore, in step (1), based on the total amount of monomer I and monomer II, the amount of monomer I is 1-3 wt%.
[0097] Furthermore, based on the total amount of monomer I and monomer II, the amount of emulsifier is 0.01-0.05wt%, the amount of initiator is 0.01-0.05wt%, and the amount of surfactant is 0.1-0.5wt%.
[0098] According to the present invention, in step (2), the amount of formula I is 1-10 wt % based on the total amount of monomer I and monomer III.
[0099] According to the present invention, based on the total amount of monomer I and monomer III, the amount of emulsifier is 0.01-0.1wt%, the amount of initiator is 0.01-0.1wt%, the amount of surfactant is 0.01-1wt%, and the amount of carbon nanotubes is 0.5-15wt%.
[0100] In the present invention, when the amount of each substance is controlled to meet the above-mentioned range, the content of the structural unit from monomer I (the structural unit shown in Formula 1) in the prepared foamable polylactic acid bead material can be moderate, sufficient to react with the structural unit from monomer I in polymer A, and the colloidal particles in the emulsion and the polymer A emulsion have excellent stability, ensuring that the content of the conductive agent loaded by polymer B is increased, thereby improving the conductive properties in the foamable polylactic acid bead material while ensuring the stability of the polymer B emulsion.
[0101] Furthermore, in step (2), based on the total amount of monomer I and monomer III, the amount of formula I is 1-3 wt%.
[0102] Furthermore, based on the total amount of monomer I and monomer III, the amount of emulsifier is 0.01-0.05wt%, the amount of initiator is 0.01-0.05wt%, the amount of surfactant is 0.1-0.5wt%, and the amount of carbon nanotubes is 3-10wt%.
[0103] According to the present invention, the solid content of the emulsion A is 10-50 wt %.
[0104] In the present invention, when the solid content of emulsion A is controlled to meet the above range, emulsion A has a lower viscosity and is easier to be uniformly mixed with emulsion B.
[0105] Furthermore, the solid content of the emulsion A is 25-35wt%.
[0106] According to the present invention, the solid content of the emulsion B is 10-50 wt%.
[0107] In the present invention, when the solid content of emulsion B is controlled to meet the above range, emulsion B has a lower viscosity and is easier to be uniformly mixed with emulsion A.
[0108] Furthermore, the solid content of the emulsion B is 25-35wt%.
[0109] According to the present invention, in step (3), the amount of polylactic acid particles used is 150-190 parts by mass, the amount of emulsion A used is 30-50 parts by mass, and the amount of emulsion B used is 30-50 parts by mass.
[0110] In the present invention, when the masses of the polylactic acid particles, emulsion A and emulsion B are controlled to meet the above-mentioned range, the emulsion A and emulsion B can fully fill the gaps between the polylactic acid particles, increase the filling amount of the conductive agent, and after drying and removing the solvent (water), the polymer A in the emulsion A and the polymer B in the emulsion B filled in the gaps between the polylactic acid particles can significantly improve the bonding ability between the polylactic acid particles, ultimately making the foamable polylactic acid bead material have excellent bonding properties and conductive properties.
[0111] Furthermore, in step (3), the amount of polylactic acid particles used is 170-180 parts by mass, the amount of emulsion A used is 40-50 parts by mass, and the amount of emulsion B used is 40-50 parts by mass.
[0112] According to the present invention, the initiators in step (1) and step (2) are added independently in the form of solutions.
[0113] In a specific embodiment of the present invention, in step (1), in the presence of water, an emulsifier and a surfactant, after adding monomer I and 20-40wt% of monomer II, 45-55wt% of initiator is added, and the reaction is carried out at 60-70°C for 0.5-1h, and then the remaining monomer II and the remaining initiator are added, and the reaction is carried out at 70-90°C for 1-2h.
[0114] In the present invention, the emulsion A is prepared in the above-mentioned specific manner to achieve stable control of the reaction rate, so that the monomer I has a high conversion rate during the polymerization process and the polymer A obtained by polymerization has a suitable molecular weight.
[0115] In a specific embodiment of the present invention, in step (2), in the presence of water, an emulsifier and a surfactant, carbon nanotubes, monomer I and 20-40wt% of monomer III are added, and then 45-55wt% of an initiator is added, and the reaction is carried out at 60-70°C for 0.5-1h, and then the remaining monomer III and the remaining initiator are added, and the reaction is carried out at 70-90°C for 1-2h.
[0116] In the present invention, the emulsion B is prepared in the above-mentioned specific manner to achieve stable control of the reaction rate, so that the monomer I has a high conversion rate during the polymerization process and the polymer B obtained by polymerization has a suitable molecular weight.
[0117] The third aspect of the present invention provides a foamed polylactic acid bead material, wherein the foamed polylactic acid bead material is obtained by foaming the above-mentioned foamable polylactic acid bead material.
[0118] In the present invention, the foamed polylactic acid bead material prepared by foaming the above-mentioned foamable polylactic acid bead material can have both high foaming performance and excellent conductive performance.
[0119] The fourth aspect of the present invention provides a method for preparing the above-mentioned foamed polylactic acid bead material, wherein the preparation method comprises:
[0120] A foaming agent is mixed with the above-mentioned expandable polylactic acid bead material, and foamed to obtain the foamed polylactic acid bead material.
[0121] According to the present invention, the foaming agent is selected from at least one of CO2, N2, 1,1-dichloro-2-fluoroethylene (C2HCl2F), and 1,2-dichlorofluoroethane (C2H3F2Cl); preferably, the foaming agent is CO2.
[0122] According to the present invention, the foaming conditions include: a foaming pressure of 5-30 MPa, and a foaming time of 2-24 h.
[0123] Furthermore, the foaming conditions include: a foaming pressure of 12-17 MPa and a foaming time of 3-5 h.
[0124] In one specific embodiment of the present invention, the method for preparing the foamed polylactic acid bead material comprises:
[0125] In the first step, a surfactant (polyvinyl alcohol) is dissolved in deionized water under stirring and heating conditions to obtain a clear solution;
[0126] Under stirring conditions, an emulsifier is added to the cooled clear solution to fully dissolve the emulsifier, and then monomer I and 20-40 wt% of monomer II are added, followed by 45-55 wt% of initiator, and the mixture is reacted at 60-70° C. for 0.5-1 h, and then the remaining monomer II and the remaining initiator are added, and the mixture is reacted at 70-90° C. for 1-2 h. During the reaction, the pH value of the reaction system is controlled to be 3-5, and an emulsion A is obtained. Preferably, the stirring rate is 500-1500 rpm, and the heating temperature is 85-95° C.
[0127] In the second step, the surfactant (polyvinyl alcohol) is dissolved in deionized water under stirring and heating conditions to obtain a clear solution;
[0128] Under stirring conditions, an emulsifier is added to the cooled clear solution to fully dissolve the emulsifier, and then carboxyl-modified carbon nanotubes, monomer I and 20-40wt% of monomer III are added, and then 45-55wt% of initiator is added, and after reacting at 60-70°C for 0.5-1h, the remaining monomer III and the remaining initiator are added, and reacting at 70-90°C for 1-2h, and the pH value of the reaction system is controlled to be 3-5 during the reaction to obtain emulsion B. Preferably, the stirring rate is 500-1500rpm, and the heating temperature is 85-95°C.
[0129] In the third step, 150-190 parts by mass of PLA raw material particles are filled in the mold. Subsequently, 30-50 parts by mass of emulsion A obtained in the first step and 30-50 parts by mass of emulsion B obtained in the third step are mixed and poured into the mold so that the mixed emulsion fully fills the gaps between the PLA raw material particles. The mold is placed in an oven at 50-70°C and dried for 4-8 hours. Finally, 170-220 parts by mass of expandable polylactic acid beads are taken out from the mold and obtained.
[0130] In the fourth step, 170-220 parts by mass of the expandable polylactic acid bead material prepared in the third step is placed in a high-pressure reactor, 5-30 MPa of CO2 is injected into the reactor through a booster pump, and the pressure is maintained for 2-24 hours to allow the CO2 to fully dissolve and diffuse in the expandable polylactic acid bead material. Subsequently, the pressure is quickly released to normal pressure to obtain the expandable polylactic acid bead material.
[0131] Figure 1 The diagram is a schematic diagram of the formation of a confined space CNT conductive path in the foamed polylactic acid bead material of the present invention. The continuous space between the PLA beads is filled with a mixture of an emulsion A containing polymer A and an emulsion B containing CNT-wrapped polymer B particles. The water therein gradually evaporates, the flexible polymers A contact and fuse with each other to form a new matrix film, and the CNT-wrapped polymer B particles are in the flexible polymer A matrix. The CNTs on the surface of the polymer B particles contact with each other to form a conductive path in the entire foamed polylactic acid bead material.
[0132] The present invention will be described in detail below through examples. In the following examples, the temperature parameters are measured by thermocouples;
[0133] The pH parameter was measured by pH meter method;
[0134] The polylactic acid raw material was a commercial product of Nature Works with a brand number of 4032D and an average particle size of 3.2 mm.
[0135] The polyvinyl alcohol raw material is a commercial product of the company with brand name;
[0136] The raw material of sodium dodecyl sulfate was a commercial product of Aladdin Company with the brand name AR;
[0137] The raw material of ammonium persulfate is a commercial product of Aladdin Company with the brand AR; the raw materials of methyl methacrylate and butyl methacrylate are commercial products of Aladdin Company with the brand AR;
[0138] The raw materials of ethyl acrylate and butyl acrylate are commercially available products with the brand name AR from Aladdin Company;
[0139] The TMSPMA raw material was a commercial product of TCI with the brand name AR;
[0140] The sodium bicarbonate raw material is a commercial product of Aladdin Company with the brand name AR;
[0141] The carboxylated CNT raw material is a commercial product of Nanjing Xianfeng Nano Co., Ltd. with a brand name of XFS18, wherein the content of carboxyl groups is 9 wt %.
[0142] Example 1
[0143] The first step is to weigh 1 part by mass of PVA and dissolve it in 30 parts by mass of deionized water, stir, and slowly heat it to about 90°C. Stir at a constant temperature for 30 minutes. Dissolve PVA completely into a clear solution. Cool to room temperature for use. Add the above PVA solution and 0.2 parts by mass of SDS to a three-necked flask equipped with a mechanical stirrer and a reflux condenser, and completely dissolve SDS at a stirring rate of 1000rpm. Add 4 parts by mass of EA (33wt% of monomer II) and 0.2 parts by mass of TMSPMA (monomer I) under stirring at 1000rpm. Dissolve 0.1 parts by mass of APS in 1.9 parts by mass of deionized water to obtain 2 parts by mass of initiator solution. First, take only 1 part by mass of the initiator solution (50wt% of the initiator) and add it to the reaction bottle. Heat the three-necked flask in a water bath and control the reaction temperature at 65°C. Pour 8 parts by mass of EA into the reaction bottle within 30 minutes using a dropping funnel. During the reaction, the solution becomes acidic due to the decomposition of the initiator, and a 5% sodium bicarbonate solution is used to maintain the pH of the reaction system to 4. The remaining 1 part by mass of the initiator solution is added. After the feeding is completed, continue heating and reflux. The temperature is raised to 80°C and the reaction is carried out for 90 minutes to obtain 45.4 parts by mass of emulsion A1, wherein, based on the total amount of monomer I and monomer II, the amount of monomer I is 1.6wt%, the amount of monomer II is 98.4wt%, the amount of surfactant (PVA) is 8.2wt%, the amount of emulsifier (SDS) is 1.64wt%, the amount of initiator (APS) is 0.82wt%, and the solid content of emulsion A1 is 29.7wt%.
[0144] In the second step, 1 part by mass of PVA is dissolved in 30 parts by mass of deionized water, stirred, and slowly heated to about 90°C. Stir at constant temperature for 30 minutes. The PVA is completely dissolved into a clear solution. Cool to room temperature for use. Add the above PVA solution and 0.2 parts by mass of SDS to a three-necked flask equipped with a mechanical stirrer and a reflux condenser, completely dissolve the SDS at a stirring rate of 1000rpm, and then add 0.2 parts by mass of carboxylated CNT to form a stable suspension. Add 4 parts by mass of MMA (33wt% of monomer III) and 0.2 parts by mass of TMSPMA at a stirring rate of 1000rpm. Dissolve 0.1 parts by mass of APS in 1.9 parts by mass of deionized water to obtain 2 parts by mass of initiator solution. First, only 1 part by mass of the initiator solution (50wt% of the initiator) is added to the reaction bottle. Heat the three-necked flask in a water bath and control the reaction temperature at 65°C. Pour 8 parts by mass of MMA into the reaction bottle using a dropping funnel within 30 minutes. During the reaction, the solution becomes acidic due to the decomposition of the initiator, and the pH of the reaction system is maintained at 4 with a 5% sodium bicarbonate solution. Add the remaining 1 part by mass of the initiator solution. After the feeding is completed, continue heating and reflux. Heat to 80°C, react for 90 minutes, and obtain 45.6 parts by mass of emulsion B1, wherein, based on the total amount of monomer I and monomer III, the amount of monomer I is 1.6wt%, the amount of conductive agent is 1.64wt%, the amount of surfactant (PVA) is 8.2wt%, the amount of emulsifier (SDS) is 1.64wt%, the amount of initiator (APS) is 0.82wt%, and the solid content of emulsion B1 is 30.1wt%.
[0145] In the third step, 170 parts by mass of PLA raw material particles were filled in the mold. Subsequently, 45.4 parts by mass of emulsion A1 obtained in the first step and 45.6 parts by mass of emulsion B1 obtained in the second step were mixed and poured into the mold so that the mixed emulsion fully filled the gaps between the PLA raw material particles. The mold was placed in an oven at 60°C and dried for 2 hours. Finally, 195 parts by mass of expandable polylactic acid bead material A1 was taken out from the mold.
[0146] In the fourth step, 195 parts by weight of the expandable polylactic acid bead material prepared in the third step was placed in an autoclave, heated to 100°C, and 15MPa of CO2 was injected into the autoclave through a booster pump, and maintained for 4 hours to allow the CO2 to fully dissolve and diffuse in the conductive PLA product. Subsequently, the pressure was quickly released to normal pressure to obtain 195 parts by weight of the expandable polylactic acid bead material EPLA-1.
[0147] Figure 2 The following are photos of various stages of the preparation process of the expanded polylactic acid bead material EPLA-1 in Example 1. Figure 2(a)) was placed in a mold bottle and poured into the emulsion A1 and emulsion B1 in Example 1. It can be observed that the black mixed emulsion can flow and fill the gaps between the PLA beads (such as Figure 2 (b)). When the water in the emulsion evaporates, polymer A and carbon nanotube-coated polymer B particles form a continuous sintered layer to obtain a foamable polylactic acid bead material (such as Figure 2 The material was placed in a supercritical CO2 foaming reactor, and 15MPa of CO2 was injected into it through a booster pump, and the foaming temperature was maintained at 110°C for 4 hours to allow CO2 to fully dissolve and diffuse in the conductive EPLA product. Subsequently, the pressure was quickly released to normal pressure to obtain a polylactic acid foamed bead material (such as Figure 2 (d)). Figure 2 (d) It can be seen that the sample expands to a certain extent after foaming, but still maintains the molded shape.
[0148] Example 2
[0149] The first step is the same as the first step of Example 1 to obtain emulsion A1.
[0150] The second step was carried out according to the second step of Example 1, except that the amount of CNT was 0.1 parts by weight, and 45.5 parts by weight of emulsion B2 was obtained, wherein the solid content of emulsion B2 was 30wt%. Based on the total amount of monomer I and monomer III, the amount of monomer I was 1.6wt%, the amount of conductive agent was 0.82wt%, the amount of surfactant (PVA) was 8.2wt%, the amount of emulsifier (SDS) was 1.64wt%, and the amount of initiator (APS) was 0.82wt%.
[0151] In the third step, 170 parts by mass of PLA raw material particles are filled in the mold. Subsequently, 45.4 parts by mass of emulsion A1 obtained in the first step and 45.5 parts by mass of emulsion B2 obtained in the third step are mixed and poured into the mold so that the mixed emulsion fully fills the gaps between the PLA raw material particles. The mold is placed in an oven at 60°C and dried for 2 hours. Finally, 194 parts by mass of expandable polylactic acid bead material A2 is taken out from the mold.
[0152] The fourth step is the same as the fourth step of Example 1, to prepare the expanded polylactic acid bead material EPLA-2.
[0153] Example 3
[0154] The first step is the same as the first step of Example 1 to obtain emulsion A1.
[0155] The second step was carried out according to the second step of Example 1, except that the amount of CNT was 1.5 parts by weight, and 46.9 parts by weight of emulsion B3 was obtained, wherein the solid content of emulsion B3 was 31.6wt%. Among them, based on the total amount of monomer I and monomer III, the amount of monomer I was 1.6wt%, the amount of conductive agent was 12.3wt%, the amount of surfactant (PVA) was 8.2wt%, the amount of emulsifier (SDS) was 1.64wt%, and the amount of initiator (APS) was 0.82wt%.
[0156] In the third step, 170 parts by mass of PLA raw material particles were filled in the mold. Subsequently, 45.4 parts by mass of emulsion A1 obtained in the first step and 46.9 parts by mass of emulsion B3 obtained in the second step were mixed and poured into the mold so that the mixed emulsion fully filled the gaps between the PLA raw material particles. The mold was placed in an oven at 60°C and dried for 2 hours. Finally, 196 parts by mass of expandable polylactic acid bead material A3 was taken out from the mold.
[0157] The fourth step is the same as the fourth step of Example 1, and a foamed polylactic acid bead material EPLA-3 is obtained.
[0158] Example 4
[0159] The first step is the same as the first step of Example 1 to obtain emulsion A1.
[0160] The second step is the same as the second step of Example 1 to obtain emulsion B1.
[0161] In the third step, 200 parts by mass of PLA raw material particles were filled in the mold. Subsequently, 45.4 parts by mass of emulsion A1 obtained in the first step and 45.6 parts by mass of emulsion B1 obtained in the second step were mixed and poured into the mold so that the mixed emulsion fully filled the gaps between the PLA raw material particles. The mold was placed in an oven at 60°C and dried for 2 hours. Finally, 224 parts by mass of expandable polylactic acid bead material A4 were taken out from the mold.
[0162] The fourth step is carried out according to the fourth step of Example 1, except that the amount of the foamable polylactic acid bead material is 224 parts by mass, and the foamed polylactic acid bead material EPLA-4 is prepared.
[0163] Example 5
[0164] The first step is to weigh 0.6 parts by mass of PVA and dissolve it in 20 parts by mass of deionized water, stir, and slowly heat it to about 90°C. Stir at a constant temperature for 30 minutes. Dissolve the PVA completely into a clear solution. Cool to room temperature for use. Add the above PVA solution and 0.2 parts by mass of SDS to a three-necked flask equipped with a mechanical stirrer and a reflux condenser, and completely dissolve the SDS at a stirring rate of 1000rpm. Add 3 parts by mass of EA (37.5wt% of monomer II) and 0.2 parts by mass of TMSPMA under stirring at 1000rpm. Dissolve 0.1 parts by mass of APS in 1.9 parts by mass of deionized water to obtain 2 parts by mass of initiator solution. First, take only 1 part by mass of the initiator solution (50wt% of the initiator) and add it to the reaction bottle. Heat the three-necked flask in a water bath and control the reaction temperature at 65°C. Pour 5 parts by mass of EA into the reaction bottle within 30 minutes using a dropping funnel. During the reaction, the solution becomes acidic due to the decomposition of the initiator, and a 5% sodium bicarbonate solution is used to maintain the pH of the reaction system to 4. The remaining 1 mass part of the initiator solution is added. After the feeding is completed, continue heating and reflux. The temperature is raised to 80°C and the reaction is carried out for 90 minutes to obtain 30.9 mass parts of emulsion A5, wherein, based on the total amount of monomer I and monomer II, the amount of monomer I is 2.4wt%, the amount of monomer II is 97.6wt%, the amount of surfactant (PVA) is 7.3wt%, the amount of emulsifier (SDS) is 2.44wt%, the amount of initiator (APS) is 1.22wt%, and the solid content of emulsion A5 is 29.3wt%.
[0165] In the second step, 0.6 parts by mass of PVA was dissolved in 20 parts by mass of deionized water, stirred, and slowly heated to about 90°C. Stir at constant temperature for 30 minutes. The PVA was completely dissolved into a clear solution. Cool to room temperature for use. The above PVA solution and 0.2 parts by mass of SDS were added to a three-necked flask equipped with a mechanical stirrer and a reflux condenser, and the SDS was completely dissolved at a stirring rate of 1000 rpm, and then 0.2 parts by mass of carboxylated CNT were added to form a stable suspension. 3 parts by mass of MMA (37.5wt% of monomer II) and 0.2 parts by mass of TMSPMA were added at a stirring rate of 1000 rpm. 0.1 parts by mass of APS were dissolved in 1.9 parts by mass of deionized water to obtain 2 parts by mass of initiator solution. First, only 1 part by mass of the initiator solution (50wt% of the initiator) was added to the reaction bottle. The three-necked flask was heated in a water bath to control the reaction temperature at 65°C. Pour 5 parts by mass of MMA into the reaction bottle using a dropping funnel within 30 minutes. During the reaction, the solution becomes acidic due to the decomposition of the initiator, and the pH of the reaction system is maintained at 4 with a 5% sodium bicarbonate solution. Add the remaining 1 part by mass of the initiator solution. After the feeding is completed, continue heating and reflux. Heat to 80°C, react for 90 minutes, and obtain 31.2 parts by mass of emulsion B5. Based on the total amount of monomer I and monomer III, the amount of monomer I is 2.4wt%, the amount of monomer III is 97.6wt%, the amount of carbon nanotubes is 2.44wt%, the amount of surfactant (PVA) is 7.3wt%, the amount of emulsifier (SDS) is 1.22wt%, the amount of initiator (APS) is 1.22wt%, and the solid content of emulsion B5 is 29.8wt%.
[0166] The third step is the same as the third step of Example 1, and 186 parts by mass of expandable polylactic acid bead material A5 are obtained.
[0167] The fourth step is the same as the fourth step of Example 1, and a foamed polylactic acid bead material EPLA-5 is prepared.
[0168] Example 6
[0169] The first step is the same as the first step of Example 5 to obtain emulsion A5.
[0170] The second step was carried out according to the second step of Example 5, except that the amount of CNT was 0.1 parts by weight, and 31.1 parts by weight of emulsion B6 were obtained, wherein the solid content of emulsion B6 was 29.4wt%. Based on the total amount of monomer I and monomer III, the amount of monomer I was 2.4wt%, the amount of monomer III was 97.6wt%, the amount of carbon nanotubes was 1.22wt%, the amount of surfactant (PVA) was 7.3wt%, the amount of emulsifier (SDS) was 1.22wt%, and the amount of initiator (APS) was 1.22wt%.
[0171] The third step is the same as the third step of Example 5, except that emulsion B6 is used to replace emulsion B5 to obtain foamable polylactic acid bead material A6.
[0172] The fourth step is the same as the fourth step of Example 5, and a foamed polylactic acid bead material EPLA-6 is prepared.
[0173] Example 7
[0174] The first step is referred to the first step of Example 1, except that the amount of TMSPMA is 0.1 parts by weight, and 45.3 parts by weight of emulsion A7 are obtained, wherein the solid content of emulsion A7 is 29.6wt%. Based on the total amount of monomer I and monomer II, the amount of monomer I is 0.8wt%, the amount of monomer II is 99.2wt%, the amount of surfactant (PVA) is 8.3wt%, the amount of emulsifier (SDS) is 1.65wt%, and the amount of initiator (APS) is 0.83wt%.
[0175] The second step is the same as the first step of Example 1 to obtain emulsion B1.
[0176] The third step is to refer to the third step of Example 1, except that emulsion A7 is used instead of emulsion A1 to obtain foamable polylactic acid bead material A7.
[0177] The fourth step is the same as the fourth step of Example 1, to prepare the expanded polylactic acid bead material EPLA-7.
[0178] Example 8
[0179] The first step is the same as the first step of Example 1 to obtain emulsion A1.
[0180] In the second step, the first step of Example 1 was referred to, except that the amount of TMSPMA was 0.1 parts by weight, and 45.6 parts by weight of emulsion B8 was obtained, wherein the solid content of emulsion B8 was 30 wt%. Wherein, based on the total amount of monomer I and monomer III, the amount of monomer I was 0.8 wt%, the amount of conductive agent was 1.65 wt%, the amount of surfactant (PVA) was 8.3 wt%, the amount of emulsifier (SDS) was 1.65 wt%, and the amount of initiator (APS) was 0.83 wt%.
[0181] The third step is to refer to the third step of Example 1, except that emulsion B8 is used instead of emulsion B1 to obtain foamable polylactic acid bead material A8.
[0182] The fourth step is the same as the fourth step of Example 1, and a foamed polylactic acid bead material EPLA-8 is prepared.
[0183] Example 9
[0184] The first step is the same as the first step of Example 1 to obtain emulsion A1.
[0185] The second step is the same as the second step of Example 5 to obtain emulsion B5.
[0186] The third step is as in the third step of Example 1, except that emulsion B5 is used instead of emulsion B1 to obtain foamable polylactic acid bead material A9.
[0187] The fourth step is the same as the fourth step of Example 1. A foamed polylactic acid bead material EPLA-9 is obtained.
[0188] Comparative Example 1
[0189] The first step is the same as the first step in Example 1.
[0190] In the second step, the same method as in the second step of Example 1 is used, except that no CNT is added, to obtain emulsion DB1.
[0191] The third step is carried out according to the third step of Example 1, except that the emulsion B1 is replaced by the emulsion DB1 to obtain the foamable polylactic acid bead material D1.
[0192] The fourth step is the same as the fourth step of Example 1, to obtain the foamed polylactic acid bead material EPLA-D1.
[0193] Comparative Example 2
[0194] In the first step, 1 part by mass of PVA is dissolved in 30 parts by mass of deionized water, stirred, and slowly heated to about 90°C. Stir at constant temperature for 30 minutes. The PVA is completely dissolved into a clear solution. Cool to room temperature for use. Add the above PVA solution and 0.2 parts by mass of SDS to a three-necked flask equipped with a mechanical stirrer and a reflux condenser, completely dissolve the SDS at a stirring rate of 1000rpm, and then add 0.2 parts by mass of carboxylated CNT to form a stable suspension. Add 4 parts by mass of EA and 0.2 parts by mass of TMSPMA under stirring at 1000rpm. Dissolve 0.1 parts by mass of APS in 1.9 parts by mass of deionized water to obtain 2 parts by mass of initiator solution. First, only 1 part by mass of the initiator solution is added to the reaction bottle. The three-necked flask is heated in a water bath to control the reaction temperature at 65°C. Pour 8 parts by mass of EA into the reaction bottle within 30 minutes using a dropping funnel. During the reaction, the solution was acidic due to the decomposition of the initiator, and a 5% sodium bicarbonate solution was used to maintain the pH of the reaction system to 4. The remaining 1 mass part of the initiator solution was added. After the feeding was completed, heating and reflux were continued. The temperature was raised to 80°C and the reaction was carried out for 90 minutes to obtain 45.6 mass parts of emulsion, wherein the solid content of the emulsion was 30.1wt%, wherein, based on the total amount of monomer I and monomer II, the amount of monomer I was 1.6wt%, the amount of monomer II was 98.4wt%, the amount of surfactant (PVA) was 8.2wt%, the amount of emulsifier (SDS) was 1.64wt%, the amount of initiator (APS) was 0.82wt%, and the amount of carboxylated CNT was 1.64wt%.
[0195] In the second step, 170 parts by mass of PLA raw material particles were filled in the mold. Subsequently, 45.6 parts by mass of the emulsion obtained in the first step was poured into the mold so that the emulsion fully filled the gaps between the PLA raw material particles. The mold was placed in an oven at 60°C and dried for 2 hours. Finally, 178 parts by mass of expandable polylactic acid bead material D2 was taken out from the mold.
[0196] The third step is the same as the fourth step of Example 1, to prepare the expanded polylactic acid bead material EPLA-D2.
[0197] Comparative Example 3
[0198] The first step is the same as the first step of Example 1 except that TMSPMA is not added.
[0199] The second step is the same as the second step of Example 1 except that TMSPMA is not added.
[0200] The third step is the same as the third step of Example 1, to obtain expandable polylactic acid bead material D3.
[0201] The fourth step is the same as the fourth step of Example 1. A foamed polylactic acid bead material EPLA-D3 is obtained.
[0202] Comparative Example 4
[0203] The first step is the same as the first step of Example 1. The difference is that the monomer II is hexyl acrylate.
[0204] The second step is the same as the second step of Example 1. The difference is that the monomer III is hexyl methacrylate.
[0205] The third step is the same as the third step of Example 1, to obtain expandable polylactic acid bead material D4.
[0206] The fourth step is the same as the fourth step of Example 1. A foamed polylactic acid bead material EPLA-D4 is obtained.
[0207] Comparative Example 5
[0208] The first step is the same as the first step in Example 1.
[0209] The second step is as in the second step of Example 1, except that 0.2 parts of carbon nanotubes without any surface modification are added to obtain emulsion DB5.
[0210] The third step is as described in the third step of Example 1, except that emulsion DB5 is used to replace emulsion B1 to obtain expandable polylactic acid bead material D5.
[0211] The fourth step is the same as the fourth step of Example 1. A foamed polylactic acid bead material EPLA-D5 is obtained.
[0212] Comparative Example 6
[0213] The first step is to weigh 0.5 parts by mass of PVA and dissolve it in 15 parts by mass of deionized water, stir, and slowly heat it to about 90°C. Stir at a constant temperature for 30 minutes. Dissolve the PVA completely into a clear solution. Cool to room temperature for use. Add the above PVA solution and 0.1 parts by mass of SDS to a three-necked flask equipped with a mechanical stirrer and a reflux condenser, and completely dissolve the SDS at a stirring rate of 1000rpm. Add 2 parts by mass of EA (33wt% of monomer II) and 0.1 parts by mass of TMSPMA (monomer I) under stirring at 1000rpm. Dissolve 0.05 parts by mass of APS in 0.95 parts by mass of deionized water to obtain 1 part by mass of initiator solution. First, only take 0.5 parts by mass of the initiator solution (50wt% of the initiator) and add it to the reaction bottle. Heat the three-necked flask in a water bath and control the reaction temperature at 65°C. Pour 4 parts by mass of EA into the reaction bottle within 30 minutes using a dropping funnel. During the reaction, the solution becomes acidic due to the decomposition of the initiator, and a 5% sodium bicarbonate solution is used to maintain the pH of the reaction system at 4. The remaining 0.5 parts by mass of the initiator solution is added. After the feeding is completed, heating and reflux are continued. The temperature is raised to 80°C and the reaction is carried out for 90 minutes to obtain 22.7 parts by mass of emulsion DA6, wherein, based on the total amount of monomer I and monomer II, the amount of monomer I is 1.6wt%, the amount of surfactant (PVA) is 8.2wt%, the amount of emulsifier (SDS) is 1.64wt%, the amount of initiator (APS) is 0.82wt%, and the solid content of emulsion DA6 is 29.7wt.%.
[0214] In the second step, 0.5 parts by mass of PVA was dissolved in 15 parts by mass of deionized water, stirred, and slowly heated to about 90°C. Stir at constant temperature for 30 minutes. The PVA was completely dissolved into a clear solution. Cool to room temperature for use. The above PVA solution and 0.1 parts by mass of SDS were added to a three-necked flask equipped with a mechanical stirrer and a reflux condenser, and the SDS was completely dissolved at a stirring rate of 1000 rpm, and then 0.1 parts by mass of carboxylated CNT were added to form a stable suspension. 2 parts by mass of MMA (33 wt% of monomer III) and 0.1 parts by mass of TMSPMA were added at a stirring rate of 1000 rpm. 0.05 parts by mass of APS were dissolved in 0.95 parts by mass of deionized water to obtain 1 part by mass of initiator solution. First, only 0.5 parts by mass of the initiator solution (50 wt% of the initiator) was added to the reaction bottle. The three-necked flask was heated in a water bath to control the reaction temperature at 65°C. Pour 4 parts by mass of MMA into the reaction bottle using a dropping funnel within 30 minutes. During the reaction, the solution becomes acidic due to the decomposition of the initiator, and the pH of the reaction system is maintained at 4 with a 5% sodium bicarbonate solution. Add the remaining 0.5 parts by mass of the initiator solution. After the feeding is completed, continue heating and reflux. Heat to 80°C, react for 90 minutes, and obtain 22.8 parts by mass of emulsion DB6, wherein, based on the total amount of monomer I and monomer III, the amount of monomer I is 1.6wt%, the amount of conductive agent carbon nanotubes is 1.64wt%, the amount of surfactant (PVA) is 8.2wt%, the amount of emulsifier (SDS) is 1.64wt%, the amount of initiator (APS) is 0.82wt%, and the solid content of emulsion DB6 is 30.1wt.%.
[0215] The third step is as in the third step of Example 1, except that emulsifier DA6 is used instead of emulsifier A1, and emulsifier DB6 is used instead of emulsifier B1, to obtain expandable polylactic acid bead material D6.
[0216] The fourth step is the same as the fourth step of Example 1. A foamed polylactic acid bead material EPLA-D6 is obtained.
[0217] The expandable polylactic acid bead materials obtained in the examples and comparative examples were characterized, and the results are shown in Table 1.
[0218] Table 1
[0219]
[0220]
[0221] a is the content of carbon nanotubes based on the total weight of polymer B, in wt%.
[0222] Table 1 continued
[0223] Continuous phase: dispersed phase PLA content b / wt% Adhesive layer content b / wt% CNT content c / wt% Example 1 0.99:1 65.1 34.9 0.10 Example 2 0.99:1 65.2 34.8 0.05 Example 3 0.9:1 64.8 35.2 0.77 Example 4 0.99:1 68.7 31.3 0.09 Example 5 0.98:1 73.2 26.8 0.11 Example 6 0.99:1 73.2 26.8 0.05 Example 7 0.98:1 65.2 34.8 0.10 Example 8 0.99:1 65.2 34.8 0.10 Example 9 1.45:1 68.9 31.1 0.10 Comparative Example 1 1:1 65.2 34.8 0.11 Comparative Example 2 1:0 78.9 21.1 0.10 Comparative Example 3 0.99:1 65.2 34.8 0.10 Comparative Example 4 0.99:1 65.1 34.9 0.10 Comparative Example 5 0.99:1 65.1 34.9 0.10 Comparative Example 6 0.99:1 78.9 21.1 0.05
[0224] b The total weight of the expandable polylactic acid bead material is used as a benchmark.
[0225] c The content of CNT is based on the total weight of the foamed polylactic acid bead material.
[0226] Figure 3 The optical microscope photographs of the bonding layers of different conductive polylactic acid foam beads. The black part is the CNT-coated polymer B (PMMA / TMSPMA) microbeads. The yellow part is the continuous matrix formed by polymer A (PEA / TMSPMA). The optical microscope photographs show that in the polylactic acid foam beads of the present invention, in the bonding layer between the PLA beads, a multiphase structure is formed with CNT-coated polymer B particles as the dispersed phase and polymer A as the continuous phase. The CNT-coated polymer B particles have good conductive properties. Example 1 ( Figure 3 (a)) The polymer B particles in the embodiment 3 ( Figure 3 (b)) has more contact sites for polymer B particles, which effectively increases the density of conductive paths. Figure 3 (c)) has the same CNT content as in Example 1, but the content of polymer A and polymer B is reduced, resulting in a decrease in the number of particles loaded with CNTs, and thus fewer conductive paths. Figure 3 In (d)), CNTs are only introduced into polymer A as the continuous phase, and the necessary rigid particle carrier of polymer B is lacking, making it difficult to form an effective conductive path.
[0227] Figure 4 It is a scanning electron microscope photo of the bonding layer of different conductive polylactic acid foam bead materials. Figure 4 The granular material in the embodiment is a CNT-wrapped polymer B microbead, which has a size of about 30 μm. Figure 4 (a)) The polymer B microbeads are uniformly dispersed in the continuous polymer A matrix, and the particles are in contact with each other, forming a good conductive path. Example 3 ( Figure 4 (b)) further increases the CNT content, and it can be seen that the contact sites of polymer B microbeads increase, indicating that the density of the conductive path increases. Example 5 ( Figure 4 (c)) reduces the ratio of polymer A to polymer B, so that the contact points between the particles are reduced. Figure 4In (d)), CNTs are only introduced into polymer A as the continuous phase, lacking the necessary rigid particle carrier of polymer B, and no effective conductive pathway is formed.
[0228] Figure 5 : is a scanning electron microscope photograph of the bonding layer of the polylactic acid foamed beads material in Example 1 at a magnification of 12,000 times. Figure 5 The microstructure of the surface of polymer B microbeads can be observed in the figure. The surface of the particle material is not smooth, but is wrapped by a large number of filamentous materials. The diameter of the filamentous material is 20-30nm, which should be the CNT wrapped on the surface of polymer B particles. These conductive CNTs are tightly stacked on the surface of polymer B particles. And different polymer B particles are in contact with each other, which means that the CNTs in the entire bonding layer are in contact with each other, forming a continuous high-density conductive network structure in an effective way, so that the polylactic acid foamed beads have good conductive properties.
[0229] Test Example 1
[0230] The electrical conductivity, tensile strength, compressive strength and foaming density of the polylactic acid foamed beads prepared in the examples and comparative examples were tested, and the results are shown in Table 2.
[0231] The electrical conductivity is tested using a plastic conductivity tester according to GB / T 15662-1995 standard.
[0232] The tensile strength is measured according to GB / T 9641-1988.
[0233] The compressive strength is measured according to GB / T 15048-1994.
[0234] Table 2
[0235] Conductivity (S / cm) Tensile strength(MPa) Compression strength(MPa) <![CDATA[Foaming density (g / cm 3 )]]> Example 1 <![CDATA[2.5×10 -2 ]]> 8.95 29.93 0.311 Example 2 <![CDATA[3.9×10 -5 ]]> 7.05 28.56 0.363 Example 3 <![CDATA[1.2×10 -1 ]]> 9.84 32.62 0.270 Example 4 <![CDATA[7.0×10 -4 ]]> 8.03 29.12 0.380 Example 5 <![CDATA[5.1×10 -3 ]]> 9.56 31.07 0.425 Example 6 <![CDATA[8.8×10 -5 ]]> 7.11 28.33 0.488 Example 7 <![CDATA[4.7×10 -3 ]]> 8.17 28.46 0.325 Example 8 <![CDATA[1.5×10 -4 ]]> 7.96 28.10 0.360 Example 9 <![CDATA[9.8×10 -5 ]]> 7.56 29.52 0.338 Comparative Example 1 <![CDATA[1.5×10 -15 ]]> 6.75 26.50 0.419 Comparative Example 2 <![CDATA[8.6×10 -6 ]]> 7.27 28.62 0.470 Comparative Example 3 <![CDATA[2.2×10 -5 ]]> 7.58 28.20 0.463 Comparative Example 4 <![CDATA[8.3×10 -4 ]]> 5.84 24.28 0.407 Comparative Example 5 <![CDATA[5.1×10 -7 ]]> 7.17 27.83 0.460 Comparative Example 6 <![CDATA[2.6×10 -6 ]]> 3.28 20.73 0.352
[0236] It can be seen from Table 2 that the continuous bonding layer formed by polymer A and polymer B particles coated with CNT has the effect of improving the conductivity of EPLA. The higher the CNT content, the higher the conductivity value. In Example 1, only 0.10wt% of CNT was added to make the conductivity of the polylactic acid foamed beads reach 2.5×10 -2 In Example 3, the CNT content was increased to 0.77 wt %, which could further increase the conductivity of the polylactic acid foamed beads to 1.2×10 -1 S / cm. This indicates that this method can obtain highly conductive polylactic acid foamed beads with low CNT content.
[0237] It can be seen from Example 7 that reducing the proportion of the dispersed phase (polymer B particles coated with carbon nanotubes) will lead to a decrease in the conductivity of the polylactic acid foamed beads material.
[0238] In addition, it can be seen from Comparative Example 1 that without adding CNT, the conductivity of the polylactic acid foamed beads is 1.5×10 -15 S / cm, which is an insulating material. As can be seen from Comparative Example 2, directly adding CNT to polymer A as a bonding layer results in a significant decrease in the conductivity of the polylactic acid foamed bead material. This indicates that the bonding layer formed by using polymer A as a continuous phase and CNT-coated polymer B particles as a dispersed phase is the key to obtaining a highly conductive polylactic acid foamed bead material.
[0239] As can be seen from Example 1 and Comparative Example 1, a continuous bonding layer is formed by mixing polymer A and polymer B, and rigid CNT fibers are added, so that the polylactic acid foamed bead material obtains a reinforcing effect, resulting in a significant increase in the tensile strength and compressive strength of the polylactic acid foamed bead material. It can be found from Example 3 that the mechanical properties of the polylactic acid foamed bead material are slightly improved by continuing to increase the CNT content, indicating that under the amount of CNT added in Example 1, the polylactic acid foamed bead material has relatively ideal electrical conductivity and mechanical properties. As can be seen from Comparative Example 2, when the bonding layer lacks polymer B particles as a dispersed phase, it is difficult for CNT to form a continuous dispersion in polymer A, resulting in an insignificant fiber reinforcement effect. Suitable CNT content, with polymer A as the continuous phase and CNT-coated polymer B particles as the dispersed phase to form a bonding layer, is the key to the good mechanical properties of the polylactic acid foamed bead material.
[0240] It can be seen from Comparative Examples 3 and 5 that the lack of TMSPMA units in polymer A and polymer B, or the lack of carboxylation of carbon nanotubes, cannot form a rigid particle carrier of polymer B. Carbon nanotubes are randomly dispersed in the matrix, making it difficult to form an effective conductive path, and the conductivity is low.
[0241] It can be seen from Comparative Example 6 that the amount of polymer A and polymer B added is too small to fill the gaps between the polylactic acid beads, resulting in low efficiency of the formed conductive path and low conductivity.
[0242] From Comparative Example 5, it can be seen that after the monomers of polymer A and polymer B are changed to larger volumes of hexyl acrylate and hexyl methacrylate, the polymerization rate during the emulsion polymerization process decreases, the degree of polymerization is low, the ability to bond the polylactic acid particles is weak, and the mechanical properties are greatly reduced. From Comparative Example 6, it can be seen that the addition amount of polymer A and polymer B is too small, it is difficult to fill the gaps between the polylactic acid beads, which becomes a defect in the polylactic acid foaming bead material, resulting in a significant decrease in mechanical properties.
[0243] It can be seen from Comparative Example 4 that after the monomers of polymer A and polymer B are changed to larger volumes of hexyl acrylate and hexyl methacrylate, the polymerization rate during emulsion polymerization decreases and the degree of polymerization is low, resulting in weak bonding between the TMSPMA units of the molecular chain and the carboxylated carbon nanotubes, poor conductive path formation, and low conductivity.
[0244] Test Example 2
[0245] The expandable polylactic acid bead materials of the embodiment and the comparative example were placed in a supercritical CO2 foaming reactor and foamed at different foaming temperatures. The density values of the samples were tested using a true density meter. The results are shown in Table 3.
[0246] Table 3
[0247]
[0248]
[0249] It can be seen from Table 3 that the samples of the embodiments and the comparative examples can be prepared into foamed materials with relatively low density between 100°C and 120°C. The foaming density is lower than 0.5 g / cm 3 , indicating that polymer A and polymer B can be used as bonding layers to prepare low-density polylactic acid foamed bead materials. Among them, 110℃ is a more suitable foaming temperature. When the foaming temperature is 100℃, the melt viscosity is low and the resistance to cell growth is large; when the foaming temperature is 120℃, the melt viscosity is too high and the foaming gas is easy to escape. Therefore, the density value of the obtained foamed material is lower than that of the foamed material at 110℃. In addition, the CNT content in the bonding layer of polymer A and polymer B will also affect the foaming performance of EPLA. As can be seen from Table 1, the higher the CNT content, the lower the density of the obtained EPLA foamed material. This is mainly because the melting point of polymer A in the bonding layer is low. At the temperature suitable for PLA foaming, its melt viscosity is low, which easily leads to the escape of foaming gas, resulting in an increase in foaming density. After adding CNT, the expandability of the bonding layer can be improved to prevent the escape of foaming gas. Therefore, adding CNT to the bonding layer is beneficial to improving the foaming ability of the foamable polylactic acid bead material.
[0250] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A foamable polylactic acid bead material, characterized in that: The expandable polylactic acid bead material comprises polylactic acid particles and a bonding layer filled between the polylactic acid particles; The bonding layer includes a continuous phase and a dispersed phase, wherein the polymer A constituting the continuous phase includes a structural unit shown in Formula 1 and a structural unit shown in Formula 2, and the dispersed phase is a polymer B coated with a conductive agent, and the polymer B includes a structural unit shown in Formula 1 and a structural unit shown in Formula 3; Wherein, R1 is a C3-C5 alkylene group, R2 is a C1-C3 alkyl group, R3 is a C2-C4 alkyl group, and R4 is a C1-C4 alkyl group; The conductive agent is a conductive agent modified with functional groups; Based on the total weight of the expandable polylactic acid bead material, the content of the polylactic acid particles is 50-75wt%, and the content of the bonding layer is 25-50wt%.
2. The expandable polylactic acid bead material according to claim 1, wherein: R1 is a C3 alkylene group, R2 is a methyl group, R3 is an ethyl group, and R4 is a methyl group; Preferably, based on the total weight of polymer A, the content of the structural unit represented by formula 1 is 3-10wt%, and the content of the structural unit represented by formula 2 is 90-97wt%; Preferably, based on the total weight of polymer B, the content of the structural unit represented by formula 1 is 3-10 wt %, and the content of the structural unit represented by formula 2 is 90-97 wt %.
3. The expandable polylactic acid bead material according to claim 1 or 2, wherein: The polymer B is in granular form with an average particle size of 5-200 μm; Preferably, based on the total weight of polymer B, the content of the conductive agent is 0.5-15wt%; Preferably, the functional group is selected from carboxyl and / or amine; Preferably, the conductive agent is selected from at least one of carbon nanotubes, carbon black and graphene.
4. The expandable polylactic acid bead material according to any one of claims 1 to 3, wherein: The mass ratio of the continuous phase to the dispersed phase is 0.5-1.5:1, preferably 1-1.2:1; Preferably, based on the total weight of the expandable polylactic acid bead material, the content of the polylactic acid particles is 63-75wt%, and the content of the bonding layer is 25-37wt%; Preferably, the average particle size of the polylactic acid particles is 0.1-5 mm.
5. A method for preparing the expandable polylactic acid bead material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) in the presence of water, an emulsifier and a surfactant, a monomer I represented by formula I, a monomer II represented by formula II and an initiator are mixed to carry out a first emulsion polymerization reaction to obtain an emulsion A containing a polymer A; (2) in the presence of water, an emulsifier and a surfactant, mixing a conductive agent, a monomer I represented by formula I, a monomer III represented by formula III and an initiator, and performing a second emulsion polymerization reaction to obtain an emulsion B containing a polymer B coated with carbon nanotubes; the conductive agent is a conductive agent modified with a functional group; (3) In a mold, the polylactic acid particles, emulsion A and emulsion B are mixed and dried to obtain the foamable polylactic acid bead material; Wherein, R1 is a C3-C5 alkylene group, R2 is a C1-C3 alkyl group, R3 is a C2-C4 alkyl group, and R4-R7 are each independently a C1-C4 alkyl group; The amount of polylactic acid particles used is 150-190 parts by mass, the amount of emulsion A used is 30-50 parts by mass, and the amount of emulsion B used is 30-50 parts by mass.
6. The preparation method according to claim 5, wherein: The emulsifiers in step (1) and step (2) are each independently selected from at least one of sodium dodecylbenzene sulfonate, alkylbenzene sulfonate and fatty acid salt; Preferably, the surfactants in step (1) and step (2) are each independently selected from at least one of polyvinyl alcohol, methyl cellulose and gelatin; Preferably, the initiators in step (1) and step (2) are each independently selected from at least one of ammonium persulfate, potassium persulfate and azobisisobutyronitrile; Preferably, in step (2), the functional group is selected from carboxyl and / or amine; Preferably, the conductive agent is selected from at least one of carbon nanotubes, carbon black and graphene; Preferably, the conditions of the first emulsion polymerization reaction and the second emulsion polymerization reaction independently include: reaction temperature of 60-85°C, reaction time of 2-4h, pH of 3-5; Preferably, the drying conditions include: drying temperature of 50-70° C., and drying time of 4-8 h.
7. The preparation method according to claim 5 or 6, wherein: In step (1), based on the total amount of monomer I and monomer II, the amount of monomer I is 1-10 wt%; Preferably, based on the total amount of monomer I and monomer II, the amount of emulsifier is 0.01-0.1wt%, the amount of initiator is 0.01-0.1wt%, and the amount of surfactant is 0.01-1wt%; In step (2), based on the total amount of monomer I and monomer III, the amount of monomer I is 1-10 wt%; Preferably, based on the total amount of monomer I and monomer III, the amount of emulsifier is 0.01-0.1wt%, the amount of initiator is 0.01-0.1wt%, the amount of surfactant is 0.01-1wt%, and the amount of conductive agent is 0.5-15wt%; Preferably, the solid content of the emulsion A is 10-50wt%; Preferably, the solid content of the emulsion B is 10-50 wt %.
8. The preparation method according to any one of claims 6 to 7, wherein: The initiators in step (1) and step (2) are added independently in the form of solutions; Preferably, in step (1), in the presence of water, an emulsifier and a surfactant, after adding monomer I and 20-40 wt% of monomer II, 45-55 wt% of an initiator is added, and the reaction is carried out at 60-70° C. for 0.5-1 h, and then the remaining monomer II and the remaining initiator are added, and the reaction is carried out at 70-90° C. for 1-2 h; Preferably, in step (2), in the presence of water, an emulsifier and a surfactant, after adding monomer I and 20-40wt% of monomer III, 45-55wt% of an initiator is added, and after reacting at 60-70°C for 0.5-1h, the remaining monomer III and the remaining initiator are added, and the reaction is carried out at 70-90°C for 1-2h.
9. A foamed polylactic acid bead material, characterized in that: The foamed polylactic acid bead material is obtained by foaming the foamable polylactic acid bead material according to any one of claims 1 to 4.
10. A method for preparing the foamed polylactic acid bead material according to claim 9, characterized in that: The preparation method comprises: Mixing a foaming agent with the foamable polylactic acid bead material according to any one of claims 1 to 4, and foaming to obtain the foamed polylactic acid bead material; Preferably, the blowing agent is selected from at least one of CO2, N2, 1,1-dichloro-2-fluoroethylene and 1,2-dichlorofluoroethane; Preferably, the foaming conditions include: a foaming pressure of 5-30 MPa, and a foaming time of 2-24 h.
Citation Information
Patent Citations
Preparation method of bendable polylactic acid transparent conductive film
CN114334226A
Carbon fiber / phenolic resin reinforced composite material based on conductive network
CN115960435A
High-performance conductive polylactic acid composite material with complex orientation structure and preparation method of high-performance conductive polylactic acid composite material
CN118027628A